Breaking the Bug Barrier: Exploring Cultural and Socioeconomic Factors Influencing Youth Resistance to Edible Insect Consumption in Ibadan, Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
This study investigated the resistance to edible insect consumption among youth in Ibadan, Nigeria, with a focus on cultural and socioeconomic barriers. Utilizing a cross-sectional survey design, data were collected from 385 participants aged 18-35 years through stratified random sampling. A structured questionnaire evaluated respondents' awareness, willingness to consume, and previous experiences with edible insects. The findings indicate that although 94% of participants were aware of edible insects, actual willingness to consume them was low: only 9.7% in the 18-25 age group and 18.6% in the 26-35 age group expressed a willingness to try. Furthermore, a substantial portion of the youth, 82% in the younger group and 77.9% in the older group, reported no prior experience with edible insects. Among those with prior experience, the willingness to consume insects again was minimal, with only 5.6% of the younger group and 13.7% of the older group showing renewed interest. Logistic regression analysis identified significant predictors of willingness to consume, including age group, level of awareness, and previous experience. These results highlight the critical need to address cultural and socioeconomic barriers through targeted educational programs and community engagement initiatives. Such efforts are essential for improving the acceptance of edible insects, which could contribute to enhanced food security and sustainability as non-timber forest products.